Analysis of Stakeholder Participation in the Road Rehabilitation Project in Jati Village, Garut Regency - Hermawan, Yusuf (PT FORMOSA CENDEKIA GLOBAL, 2024)
In 2022, the Public Works and Spatial Planning Office (PUPR) of Garut Regency implemented a road rehabilitation project within the Garut Regency area. One of these projects was the rehabilitation of the road in Jati Village, Tarogong Kaler District. The road rehabilitation project involved various stakeholders. However, in practice, there were still issues with the low participation of stakeholders in the Jati Village road rehabilitation project in Garut Regency. The purpose of this study is to analyze stakeholder participation in the road rehabilitation project carried out by the PUPR office of Garut Regency in the 2022 fiscal year, with the research focus on Jati Village, Tarogong Kaler District. The research design uses a qualitative approach with a descriptive method as the research method. The data collection process used interview, observation, and documentation techniques. The research results concluded that stakeholder participation in the Jati Village road rehabilitation project has not been fully realized. This is evident from the findings that show: first, in terms of the voice aspect, the delivery of ideas and suggestions from stakeholders has not been accommodated by the office. Second, in the access aspect, the government has not provided stakeholders with access to openly learn about the project. Third, in the control aspect, the level of community involvement in overseeing the project is very low. To improve the success of the road rehabilitation project, continuous support from the local government and active participation from all stakeholders are needed